Dual-modality imaging with combined scanners 1 - Beyer, Thomas (Henry Stewart Talks, 2010)
Imaging and diagnosis, Combined imaging and software fusion, Early SPECT/CT development, The SMART PET/CT, PET/MR developments, Clinical dual-modality imaging, Advances in SPECT/CT technology
Updated at 2021/03/15